NUMERICAL SIMULATION OF THE LASER WELDING - Siwek, Aleksander (Computer Science, 2013)
The model takes into consideration thermophysical and metallurgical properties of theremelting steel, laser beam parameters and boundary conditions of the process. As a resultof heating the material, in the area of laser beam operation a weld pool is being created,whose shape and size depends on convection caused by the Marangoni force. The directionof the liquid stream depends on the temperature gradient on the surface and on the chemicalcomposition as well. The model created allows to predict the weld pool shape depending onmaterial properties, beam parameters, and boundary conditions of the sample.